Breast conservation among older patients with early‐stage breast cancer: Locoregional recurrence following adjuvant radiation or hormonal therapy. Issue 11 (26th January 2021) - Tringale, Kathryn R.; Berger, Elizabeth R.; Sevilimedu, Varadan; Wen, Hannah Y.; Gillespie, Erin F.; Mueller, Boris A.; McCormick, Beryl; Xu, Amy J.; Cuaron, John J.; Cahlon, Oren; Khan, Atif J.; Powell, Simon N.; et al.
Abstract : Background: For patients with breast cancer undergoing breast‐conserving surgery (BCS), adjuvant radiation (RT) and hormonal therapy (HT) reduce the risk of locoregional recurrence (LRR). Although several studies have evaluated adjuvant HT ± RT, the outcomes of HT versus RT monotherapy remain less clear. In this study, the risk of LRR is characterized among older patients with early‐stage breast cancer following adjuvant RT alone, HT alone, neither, or both. Methods: This study included female patients from the Memorial Sloan Kettering Cancer Center (New York, New York) who were aged ≥65 years with estrogen receptor–positive (ER+)/human epidermal growth factor receptor 2–negative (HER2–) T1N0 breast cancer treated with BCS. The primary endpoint was time to LRR evaluated by Cox regression analysis. Results: There were 888 women evaluated with a median age of 71 years (range, 65‐100 years) and median follow‐up of 4.9 years (range, 0.0‐9.5 years). There were 27 LRR events (3.0%). Five‐year LRR was 11% for those receiving no adjuvant treatment, 3% for HT alone, 4% for RT alone, and 1% for HT and RT. LRR rates were significantly different between the groups ( P < .001). Compared with neither HT nor RT, HT or RT monotherapy each yielded similar LRR reductions: HT alone (HR, 0.27; 95% CI, 0.10‐0.68; P = .006) and RT alone (HR, 0.32; 95% CI, 0.11‐0.92; P = .034). Distant recurrence and breast cancer–specific survival rates did not significantly differ between groups. Conclusions: LRR risk following BCS is low among women aged ≥65 years with T1N0, ER+/HER2– breast cancer. Adjuvant RT and HT monotherapy each similarly reduce this risk; the combination yields a marginal improvement. Further study is needed to elucidate whether appropriate patients may feasibly receive adjuvant RT monotherapy versus the current standards of HT monotherapy or combined RT/HT. Abstract : Among early‐stage favorable‐risk patients with breast cancer, it remains unclear how locoregional recurrence risk is affected by adjuvant radiation therapy, endocrine therapy, neither, or both. This study shows adjuvant monotherapy yields favorable outcomes comparable to combining endocrine and radiation therapy, but forgoing both treatments may yield unacceptably high locoregional recurrence risk.